2011
DOI: 10.1097/tp.0b013e3182081333
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Proteasome Inhibition on Alloantibody-Producing Plasma Cells In Vivo

Abstract: Bortezomib depletes DSA-PCs and appears to potentiate DSA removal by PE in sensitized renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…111 in an in vivo study of the effect of bortezomib on bone marrow plasma cells in highly allosensitized kidney transplant candidates, two of three patients treated with bortezomib had a significant decrease in CD138 + antibodysecreting cells following treatment. 112 although the investigations described above are pre liminary, they are indicators that interventions directed toward decreasing Dsa production may be feasible.…”
Section: Complement Blockadementioning
confidence: 97%
“…111 in an in vivo study of the effect of bortezomib on bone marrow plasma cells in highly allosensitized kidney transplant candidates, two of three patients treated with bortezomib had a significant decrease in CD138 + antibodysecreting cells following treatment. 112 although the investigations described above are pre liminary, they are indicators that interventions directed toward decreasing Dsa production may be feasible.…”
Section: Complement Blockadementioning
confidence: 97%
“…Bortezomib has been shown to decrease alloantibody production by bone marrowderived plasma cells and increase plasma cell apoptosis with a decrease in the amount of anti-HLA antibody detected [45 ,48]. It has also been shown to cause a significant decrease in CD138 þ antibody-secreting cells [49]. It was recently observed that naturally occurring CD4 þ CD25 þ regulatory T cells were noted to be resistant to its pro-apoptotic effect and that long-term culture of CD4 þ T cells in the presence of bortezomib promoted the emergence of a regulatory T-cell population that inhibited stimulated effector T cells [50], suggesting potential clinical benefit on 'pathologic' antibody production with decreased likelihood of impact on quiescent cells.…”
Section: Bortezomibmentioning
confidence: 98%
“…Thus, rituximab per se does not lower anti-A/B blood group antibody titers [26] and therefore has always to be combined with an antibody removal procedure. Bortezomib -a proteasome inhibitor used for treatment of multiple myeloma -has recently been reported to directly target plasma cells [27]. Preliminary studies showed some effect for treatment of acute antibody-mediated rejection mediated by anti-HLA antibodies [28,29].…”
Section: Induction and Maintenance Immunosuppressionmentioning
confidence: 98%